Corporate Finance Strategy Via Tunisian Venture Capital Organisms - Dziri, Houda; Jarboui, Anis (Asian Journal of Empirical Research, 2018)
The present research work is designed to examine the Tunisian corporate case financing strategy as undertaken by the venture capital institutions, on the basis of some criteria applied during the selection process. After discussing the theoretical relationship between the venture capitalist and the entrepreneur, we are advancing an empirical model testing the influence of the venture capitalist’ selection criteria on the acceptance to finance the enterprise. Overall, the study’s reached finding, as conducted on a sample of 41 venture capital companies operating up until the end of the year 2016. In fact, the study have revealed well the significantly impact of certain adopted criteria in relation to the other criteria and it maintains that the venture capitalist’ attitude towards the investment risk.